Harnessing Technology-Enhanced Learning Tools in Promoting Education for Sustainable Development among University Students in Ekiti State, Nigeria (Unilorin Journal of Lifelong Education, 2025)
The study investigates harnessing of technology-enhanced learning tools in promoting education for sustainable development among university students in Ekiti State, Nigeria. The objectives of the study are to examine the friendliest technology-enhanced learning tool and the factors influencing the integration in promoting education for sustainable development. Descriptive design of survey type was adopted for the study. Population comprised all the students and lecturers with the sample size of twenty (20) respondents each from the selected five faculties. through purposive and systematic random sampling technique. A total of 100 respondents each were used for the study. Two research questions were formulated and answered. Two selfconstructed instruments- Students Harnessing Technology Enhanced Learning Tools Questionnaire (SHTELTQ) (r=.749) and Teachers Factors Influencing Learning Questionnaire (TFILQ) (r=.908) were used for data gathering. Data collected were analyzed using frequency counts and percentages. The findings of the study revealed that Socrative, a cloud based platform is the friendliest technology-enhanced learning tool. In conclusion, harnessing these tools empower learners to become active global citizens, equipped to build a more resilient and equitable future. Based on the findings, it was recommended that the use of Nearpod technologyenhanced learning tools should be much more encouraged amongst students in schools to access high quality teaching and learning from any place, the budget that government accrued to education should be jerked up to add colours to her influence and that government policy on technology should be implemented so that the well-designed multimedia learning materials can be more effective than traditional classroom.